Características agrometeorológicas da cultura de soja (Glycine max (L.) Merrill) variedade Candeias em Paragominas – PA - SANTOS, Ana Patrícia Ramos Araújo dos (Universidade Federal do Pará, 2012)
The local authority of Paragominas belongs to the South-east Mesorregião from Pará (03 ° 00 ' 00 ” S and 47 ° 21 ' 30 " W) where there is the whole area already altered for deforestation and pastures only waiting for being incorporated to the productive agricultural process. The culture of the soy has significant importance for the national economy, being one of the principal agricultural produce of export and generation of emblems, pertaining to the family of the leguminous plants, is adapted in a spacious belt of climates, being able to be cultivated in all the types of ground. The objective of this study is to value the conditions agrometeorológicas during the vegetative cycle of the soy at Paragominas - PA. In this area there was built a meteorological automatic tower of 4 meters of height, being the farm white Ox located to 03°02 ´ 15 " S and 47°17 ´ 56 " W and when a station was installed with measures to each (5) five minutes of the next variables: temperature of the air (Tar), specific moisture of the air (q), temperature of the ground (Tsolo), moisture of the ground (Usolo), speed of the wind (W), direction of the wind (D), solar radiation incident (Sin), solar radiation reflected (Sout), balance of radiation (Rn) and flow of heat in the ground (G) and Haste. Microclimatic variations have quite straight effects in the development of the plant. The collections when the beginning of June of 2006 was carried out between February show that the days 84, 98 and 126 were the days of bigger haste and the days 70 and 154 and 161 there was no rain. In accordance with the development of the planting we notice that in the February the beginning of April on the very specific moisture of the air maintained elevated 21,0 g/Kg. The journey of the temperature the maxim of the air was maintained between 23,5 ºC and 32,5 ºC accompanying the development of the culture. The middle temperature of the ground in three measures (5, 10 and 20 cm), noticed to itself that the temperatures are between 25 ºC to 35 ºC. In the beginning of the planting the speed of the wind was about 3 m/s decreasing, and in the end of the cultivation 2,5 was m/s. In the period of blooming the speed was maintained stable what contributes to the dispersal of pollen and seeds. The wind comes from all the directions, meantime, the wind is predominant of northeast. When the ground is still completely naked, the albedo is lifted up, since the radiation that enters in the system is same that it goes out. When the albedo begins to develop the planting it has a tendency to lessen, since the quantity of solar radiation that reaches the system part is reflected and other one absorbed by the surface. The middle moisture of the ground in three measures (10, 20 and 30 cm), where we notice that the moisture is between 0,2 m⁄m to 0,45 m⁄m. The flow of heat in the ground to 10 cm presented peaks around-135 W/m2 and 55 W/m2 (7 the 18 h) and to 20 cm he presented peaks around-25 W/m2 and 45 W/m2 (7 the 18 h). The positive sign represents transfer of heat of the air for the ground and the flow was of the surface for the most internal layers of the ground. When we analyse the appreciated evapotranspiration we notice what was inferior of what the evapotranspiration when 4,0 mm⁄dia was appreciated and the measured evapotranspiration 8,8 mm⁄dia. When we analyse the linear regression to appreciated evapotranspiration the measured evapotranspiration was lower.